Pengaruh Penerapan Sistem Manajemen Mutu ISO 9001:2015 terhadap Efisiensi Operasional dan Daya Saing Perusahaan Manufaktur di Indonesia - Chairina Amaliah Hasibuan; Arsyadona Arsyadona (Kampus Akademik Publiser, 2026)
This study aims to analyze the effect of implementing the ISO 9001:2015 Quality Management System (QMS) on operational efficiency and competitiveness in Indonesian manufacturing companies. The research uses a qualitative descriptive approach by reviewing scientific literature published between 2020 and 2024. The results indicate that ISO 9001:2015 implementation has a significant positive effect on operational efficiency through process standardization, risk-based thinking, and the Plan-Do-Check-Act (PDCA) cycle. Furthermore, companies that adopt this standard demonstrate improved product quality, higher customer satisfaction, and stronger competitive positioning in both domestic and international markets. The study concludes that ISO 9001:2015 serves as a strategic tool for Indonesian manufacturers to enhance operational performance and sustain long-term competitiveness.